The transformation of the cultural landscape of Remte manor - Ziemeļniece, Aija; Zilgalvis, Jānis (Landscape Architecture and Art, 2025)
The cultural and historical landscape of Latvia, formed by rural manor building ensembles, is increasingly attracting the attention of researchers, as it is an integral part of our cultural environment. The first half of the 21st century is marked by a new trend in the rural historical landscape of Latvia, i.e. the cessation of the exaggerated construction boom, which was associated with the development of collective and state farm centres around the manor building centre. The tendency of the occupying power was fundamentally aimed at concealing the cultural heritage buildings and disrupting the spatial structure that has historically formed the expression of the manor ensemble. This is also applicable to the Remte Manor ensemble, whose historical buildings are masterfully integrated in the picturesque natural setting - lake, terrain, forest, meadows, which are also complemented by the old trade highways located nearby. The last century has brought changes to the historically spatial structure of the manor ensemble. The current direction of the state’s economic policy contributes to the emptying of the Latvian countryside, as well as the abandonment of cultural and historical sites, creating a range of problems in their management for rural municipalities.